Development and Experimental Investigations of Motion Detection Module for Smart Lighting System; IOP Conference Series: Materials Science and Engineering; Vol. 132 : Modern Technologies for Non-Destructive Testing - Matveev I.; Siemens E.; Yurchenko A. V. Aleksey Vasilievich; Kuznetsov D. (2016, 2016)
Title screen